Effects of a new intervention based on the Health at Every Size approach for the management of obesity: The “Health and Wellness in Obesity” study - Dimitrov Ulian, Mariana; Pinto, Ana Jéssica; de Morais Sato, Priscila; B. Benatti, Fabiana; Lopes de Campos-Ferraz, Patricia; Coelho, Desire; Roble, Odilon J.; Sabatini, Fernanda; Perez, Isabel; Aburad, Luiz; Vessoni, André; Fernandez Unsain, Ramiro; et al. (PLOS ONE, 2018)
Health at Every Size® (HAES®) is a weight-neutral approach focused on promoting healthy behaviors in people with different body sizes. This study examined multiple physiological, attitudinal, nutritional, and behavioral effects of a newly developed, intensive, interdisciplinary HAES®-based intervention in obese women. This was a prospective, seven-month, randomized (2:1), controlled, mixed-method clinical trial. The intervention group (I-HAES®; n = 39) took part in an intensified HAES®-based intervention comprising a physical activity program, nutrition counseling sessions, and philosophical workshops. The control group (CTRL; n = 19) underwent a traditional HAES®-based intervention. Before and after the interventions, participants were assessed for physiological, psychological, and behavioral parameters (quantitative data) and took part in focus groups (qualitative data). Body weight, body mass index, and waist and hip circumferences did not significantly differ within or between groups (P > 0.05). I-HAES® showed increased peak oxygen uptake and improved performance in the timed-stand test (P = 0.004 and P = 0.004, between-group comparisons). No significant within- or between-group differences were observed for objectively measured physical activity levels, even though the majority of the I-HAES® participants indicated that they were engaged in or had plans to include physical activity in their routines. I-HAES® resulted in improvements in eating attitudes and practices. The I-HAES® group showed significantly improved all Body Attitude Questionnaire subscale and all Figure Rating Scale scores (P ≤ 0.05 for all parameters, within-group comparisons), whereas the CTRL group showed slight or no changes. Both groups had significant improvements in health-related quality of life parameters, although the I-HAES® group had superior gains in the “physical health,” “psychological health,” and “overall perception of quality of life and health” (P = 0.05, 0.03, and 0.02, respectively, between-group comparisons) domains. Finally, most of the quantitative improvements were explained by qualitative data. Our results show that this new intensified HAES®-based intervention improved participants’ eating attitudes and practices, perception of body image, physical capacity, and health-related quality of life despite the lack of changes in body weight and physical activity levels, showing that our novel approach was superior to a traditional HAES®-based program.